2015
DOI: 10.1037/xhp0000016
|View full text |Cite
|
Sign up to set email alerts
|

Functional fixedness: The functional significance of delayed disengagement based on attention set.

Abstract: During search, the disengagement of attention is automatically delayed when a fixated but task-irrelevant object shares features of the search target. We examined whether delayed disengagement based on top-down attention set is potentially functional, resulting in additional processing of the fixated item. To accomplish this, we adapted the oculomotor disengagement paradigm. Participants saccaded to a peripheral object of a particular color and responded to the identity of the letter within it. To initiate sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 25 publications
7
33
0
Order By: Relevance
“…If an irrelevant disk at fixation has the target color, too, it takes a bit longer to move off that disk. Building on earlier work by Wright, Boot, and Brockmole (2015), they show that the original "Functional fixedness" effect generalizes to a range of conditions.…”
Section: The Mechanics Of Searchmentioning
confidence: 57%
“…If an irrelevant disk at fixation has the target color, too, it takes a bit longer to move off that disk. Building on earlier work by Wright, Boot, and Brockmole (2015), they show that the original "Functional fixedness" effect generalizes to a range of conditions.…”
Section: The Mechanics Of Searchmentioning
confidence: 57%
“…
In a circular visual search paradigm, the disengagement of attention is automatically delayed when a fixated but irrelevant center item shares features of the target item. Additionally, if mismatching letters are presented on these items, response times (RTs) are slowed further, while matching letters evoke faster responses (Wright, Boot, & Brockmole, 2015a). This is interpreted as a functional reason of the delayed disengagement effect in terms of deeper processing of the fixation item.
…”
mentioning
confidence: 99%
“…Most et al (2005) suggested that both bottom-up stimulus properties of objects and top-down goals of the observer influence where attention is allocated, but the latter is the primary determinant of how long attention dwells on an object. More recent work is consistent with this hypothesis, as delayed disengagement of attention has been linked to goal-directed, top-down processes (e.g., Boot & Brockmole, 2010; Blakely, Wright, Dehili, Boot, & Brockmole, 2012; Wright, Boot, & Brockmole, 2015; Wright, Boot, & Jones, 2014). Most et al (2005) further suggested that IB would be more heavily influenced by top-down mechanisms (i.e., the observer’s target representation).…”
Section: Introductionmentioning
confidence: 62%
“…Consistent with this idea, top-down attention sets determine both the likelihood of noticing an unexpected distractor (Most et al, 2005) and how long attention dwells on a distractor item within fixation (Boot & Brockmole, 2010; Wright et al, 2014). Furthermore, these disengagement delays have been associated with greater depth of processing (Wright et al, 2015), critical to both recognizing and remembering a stimulus. Future work should examine the relationship between delayed attentional disengagement and noticing an unexpected stimulus.…”
Section: Discussionmentioning
confidence: 99%